Tanda Pedikulosis Kapitis pada Santriwati Sulthon Aulia Boarding School - Angga Saputra Jaya; Eka Hendyranny; Rizki Perdana (Bandung Conference Series: Medical Science, 2023)
Abstract. Pediculosis capitis is a disease caused by infection with Pediculus humanus var. capitis which is a blood-eating ectoparasites and grows on human head hair. Many factors encourage the occurrence of pediculosis capitis, including the level of knowledge about pediculosis capitis, personal hygiene, gender, socioeconomic conditions, the habit of borrowing personal items, and the density of occupants in a room. The purpose of this study was to find the signs of pediculosis capitis in female students from Sulthon Aulia Boarding School. This research method is observational with a cross-sectional design. The number of samples in this study were 120 female students. Data were taken through examination of signs of pediculosis capitis. Signs of pediculosis capitis were found in 79.2% female students. . Improper personal hygiene can increase the risk of developing pediculosis capitis. Abstrak. Pedikulosis kapitis adalah penyakit yang disebabkan oleh infeksi Pediculus humanus var. capitis yang merupakan ektoparasit pemakan darah dan tumbuh pada rambut kepala manusia. Banyak faktor yang mendorong terjadinya pedikulosis kapitis, diantaranya tingkat pengetahuan tentang pedikulosis kapitis, personal hygiene, jenis kelamin, keadaan sosial ekonomi, kebiasaan meminjam barang pribadi, dan kepadatan hunian dalam suatu ruangan. Tujuan penelitian ini yaitu untuk menilai tanda pedikulosis kapitis pada santriwati Sulthon Aulia Boarding School. Metode penelitian ini adalah observasional dengan desain cross-sectional. Jumlah sampel pada penelitian ini sebanyak 120 santriwati. Data diambil dengan dilakukannya pemeriksaan tanda pedikulosis kapitis. Ditemukan tanda pedikulosis kapitis pada 79,2% santriwati. Personal hygiene yang tidak baik dapat meningkatkan risiko terjadinya pedikulosis kapitis.